A Study on the promotion of the Ghanaian textiles industry through the Ghana trade and industrial policies - Twintoh, Francisca (KDI School, 2012)
Many governments of different countries have reformed and restrategised their policies to ensure the growth and the sustainability of their countries in attaining economic development. International Trade is said to be the cause of the boom of many economies including the miracle of the East Asian economies. It is also said that gains from trade can be possible only if the economies put in place the right measures to control certain malpractices that prevent the gains from international trade. However, for trade to be beneficial a country must capitalize on its expertise (comparative advantage) and also engage in trade in areas where it has a lesser comparative advantage by importing. This study makes a comparison of the Ghanaian textiles industry to the India and Pakistan textiles industry by benchmarking their policies and how they implemented their policy to that of Ghana. From the study conducted therefore it was revealed that for the Ghana Trade or Industrial Policies to be effective and achieve it set goals and targets there must be the presence of enhanced coordination between institutions, implementing agencies and all stakeholders of the industry. Also the benchmarking method applied to the study as shown by evidence from Pakistan and India indicated that Ghana needs to have the right framework or model for policy process and implementation in order to achieve the set goal. Finally, it was also shown that trade liberalization is a good tool for a country to attain sustainable and economic growth as well as development. The only means to ensure these benefits is that countries must put in place the right measure (regulations) and ensure that these regulations are implemented very well to check the irregularities that can ripe the benefits of the trade just as India and Pakistan did to their market.
Thesis(Master) --KDI School:Master of Public Policy,2012